Scenarios post foreclosure crisis in Catalonia: accumulation of housing by banks as the first step for the rise of large private landlords - Doménech, Antoni; Gutiérrez, Aaron; Arauzo-Carod, Josep-Maria (ERDKUNDE, 2021)
The article analyses the uneven geography of foreclosed housing owned by large private landlords in Catalonia. A Negative Binomial Model is applied to identify the local determinants of the concentration patterns of 32,941 housing units in Catalan cities. Indicators of socioeconomic vulnerability, such as the percentage of foreign population or the percentage of unemployed residents, are identified as key explanatory factors of the regional geography of housing accumulated by banks which, in turn, correspond to areas in which global corporate landlords are focusing their business for profiteering from the rental market in the current expansionist phase of the housing cycle. Our findings demonstrate that the concentration of properties in the most vulnerable areas was fuelled by foreclosures responsibility of banks rescued with public funds. In tandem, we provide detailed information for the understanding of the new scenarios that have emerged during the post-crisis phase.